Student Motivation in Learning Japanese Language Subjects at NCIPS Senior High School Kupang - Radjutuga, Maria Rosalina Oka (Japanology: The Journal of Japanese Studies, 2022)
This study analyzes the factors that influence students' motivation in learning Japanese at SMAS NCIPS Kupang. Japanese plays an important role in international relations, and understanding students' motivation is key to improving the effectiveness of learning. This research uses a quantitative approach with a survey method. A structured questionnaire was distributed to 23 students of class XII SMAS NCIPS Kupang, and classroom observation was conducted to complete the data. The results showed that there is a high enthusiasm for learning Japanese in class XII NCIPS Kupang. Factors such as enjoyment of learning, interesting learning methods, and classroom learning culture contribute to students' motivation. However, there are several factors that need to be improved, such as note-taking habits, time allocation for independent learning, and the role of parents and peers. Efforts to improve these factors can help maximize students' learning potential and improve their Japanese language proficiency.